Alàgbà Adébáyọ̀ Fálétí as a Yorùbá Novelist - Lere Adeyemi (Yoruba Studies Review)
In their introduction to a book entitled: Yorùbá creativity, fiction, language, life, and songs, Falola and Genova (2005) assert that creativity among the ̣ Yorùbá has a long history and the traditions of oral histories, storytelling, performances and dramas are parts of fundamental habit of their civilization. In the pre-colonial era, the authorship of the stories in the folktales and in some poetic genres could not be claimed by any particular artist/artiste, but due to the influence of colonial rule, western literary traditions, among others, storytellers can claim authorship of their works today. The Yorùbá make no distinction between myth, legend and history. They all come under ìtàn (Ogunsina, 1992). One Yorùbá novelist that has distinguished himself in the effective use of ìtàn (story) in novel writing is Adébáyò ̣ Fálétí. He is not only a storyteller, he is a literary historian. Every creative writer in Yorùbá society is admired and judged as competent or otherwise not only by writing in the medium of the language but by having captivating story line and on the basis of his/her use of ‘quality’ Yorùbá language (i.e. language full of proverbs and other rhetoric devices). An average Yorùbá reader of Fálétí’s novels, poetry, plays and viewer of his films usually responds with delight because of his powerful use of Yorùbá language and captivating story lines, plot construct, narrative techniques and thematic contents. Isọ la (1998) classifies all other Yorùbá major novelists apart from Fágúnwà ̣ into three groups on their use of language and creative pedigree (190). According to him, “some are mere story tellers” who use mainly casual language; 154 Lere Adeyemi there are others with mixed styles and there are a few of them who creatively exploit the genius of the language. He identifies Adébáyò ̣ Fálétí among few others as belonging to the genius category. Ogunsina (1992) groups Fálétí as a prominent historical novelist who incorporates historical materials into novel writing. I agree with Ogunsina that Fálétí’s effective transfer of histori ̣ - cal materials into fiction is a revelation of the novel’s eclectic quality and also a manifestation of Fálétí’s creative genius. Fálétí’s love of ìtàn (story) is reflected in all his literary works, be it poetry, play or novel. However, our focus in this study is to examine Adébáyọ̀ ̣ Fálétí as a Yorùbá novelist through his literary lens.